Between Legitimacy and Efficiency: An Institutional Theory of Corporate Giving - Jeong, Young-Chul; Kim, Tai-Young (Academy of Management Journal, 2019)
This study explores the cost of legitimacy management in the context of corporate giving. Specifically, how much does an organization spend in order to manage external legitimacy? We view corporate giving as a means by which firms may seek external legitimacy, and propose that, in response to evaluations of external audiences, organizations strategically manage such costs under a tension between legitimacy and efficiency concerns. We examine this argument by developing an institutional theory of corporate giving and testing our hypotheses using the corporate giving behaviors of publicly listed Korean companies from 2003 to 2011. Consistent with our proposition concerning the role of external audiences in shaping legitimacy management costs, we show that strategic decisions regarding how much a firm spends on corporate giving are related to the extent that the firm receives positive or negative media attention. Furthermore, we find that the relationship between media evaluations and corporate giving varies with a firm’s performance, which suggests that its internal efficiency condition can be an important contingency factor in determining its legitimacy management cost. We discuss the implications of these findings for the study of legitimacy management processes and the role of external audiences in such processes.